PEREMPUAN ACEH: ANTARA BUDAYA DAN SYARI'AT - Abd. Wahid (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
Acehnese women demand that the implementation of Islamic law must be suited to cultural context, Acehnese culture. The rapid change of today's lifestyle forces acehnese women to hardly preserve these two patterns; islamic law and culture. Large number of acehnese women have showed their strong commitment to live and act in form of